2019
DOI: 10.1371/journal.pone.0213474
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet induces sex-specific differential gene expression in Drosophila melanogaster

Abstract: Currently about 2 billion adults globally are estimated to be overweight and ~13% of them are obese. High fat diet (HFD) is one of the major contributing factor to obesity, heart disease, diabetes and cancer. Recent findings on the role of HFD in inducing abnormalities in neurocognition and susceptibility to Alzheimer’s disease are highly intriguing. Since fundamental molecular pathways are often conserved across species, studies involving Drosophila melanogaster as a model organism can provide insight into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
42
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 75 publications
(79 reference statements)
6
42
3
Order By: Relevance
“…Our data agree, although males survived better on HFD than did genotype-matched mated females. Previous studies showed major transcriptome differences between males and mated females reared on HFD: females upregulated fatty acid metabolism and their stress response while males downregulated stress response genes (Heinrichsen et al 2014;Stobdan et al 2019). Our data suggests that Spen-KD flies maintain this sex-specific sensitivity to dietary fat intake.…”
Section: Discussionsupporting
confidence: 53%
“…Our data agree, although males survived better on HFD than did genotype-matched mated females. Previous studies showed major transcriptome differences between males and mated females reared on HFD: females upregulated fatty acid metabolism and their stress response while males downregulated stress response genes (Heinrichsen et al 2014;Stobdan et al 2019). Our data suggests that Spen-KD flies maintain this sex-specific sensitivity to dietary fat intake.…”
Section: Discussionsupporting
confidence: 53%
“…and their stress response while males downregulated stress response genes 540 (Heinrichsen et al 2014;Stobdan et al 2019). Our data suggests that Spen-KD flies 541 maintain this sex-specific sensitivity to dietary fat intake.…”
Section: Discussion 391mentioning
confidence: 75%
“…In fruit flies, studies typically focus on whole-body or head tissue transcription (e.g. [75]); one or a few gene pathways known to affect diet responses at a time (e.g. [64]); one or two diet manipulations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[64]); one or two diet manipulations (e.g. [75][76][77]), but scarcely integrate over more than two organs and conditions at a time, or explore expression outside a few gene pathways. Further, despite costs trending downwards recently, sequencing of more highly replicated experiments remains unaffordable for many laboratories.…”
Section: Discussionmentioning
confidence: 99%